2014
DOI: 10.1186/1477-7827-12-56
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sex ratio from fertilization to birth in assisted-reproductive-treatment cycles

Abstract: BackgroundIn Western gender-neutral countries, the sex ratio at birth is estimated to be approximately 1.06. This ratio is lower than the estimated sex ratio at fertilization which ranges from 1.07 to 1.70 depending on the figures of sex ratio at birth and differential embryo/fetal mortality rates taken into account to perform these estimations. Likewise, little is known about the sex ratio at implantation in natural and assisted-reproduction-treatment (ART) cycles. In this bioessay, we aim to estimate the sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 66 publications
1
48
0
Order By: Relevance
“…In other animal-based maternal dietary models focused on the periconceptional period, gender-specific cardiometabolic or growth phenotype differences have been observed in offspring (Sinclair et al 2007;Bermejo-Alvarez et al 2011). Similarly, in assisted reproductive technology (ART)-related embryo environment models, sexual dimorphism in embryo survival and adult offspring phenotype has been recorded (Fernández-Gonzalez et al 2004;Sjöblom et al 2005;Feuer et al 2014;Tarín et al 2014). Why might this occur following dietary challenge at the preimplantation stage?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other animal-based maternal dietary models focused on the periconceptional period, gender-specific cardiometabolic or growth phenotype differences have been observed in offspring (Sinclair et al 2007;Bermejo-Alvarez et al 2011). Similarly, in assisted reproductive technology (ART)-related embryo environment models, sexual dimorphism in embryo survival and adult offspring phenotype has been recorded (Fernández-Gonzalez et al 2004;Sjöblom et al 2005;Feuer et al 2014;Tarín et al 2014). Why might this occur following dietary challenge at the preimplantation stage?…”
Section: Discussionmentioning
confidence: 99%
“…Differing environmental sensitivities by male and female embryos before gonadal development and direct sex hormone effects can be influential most likely derive from sex chromosome dosage effects on transcriptional activity (Bermejo-Alvarez et al 2011). Downstream from transcriptional differences, gender-specific variance in metabolism and growth rates may emerge in response to environmental challenge (Erickson 1997;Bermejo-Alvarez et al 2011), and this may be substantiated by X-inactivation in females (Tarín et al 2014) and by sex hormone effects during subsequent fetal development. The emergence and propagation of sexual dimorphic responses to dietary challenge from the preimplantation period onwards will be one important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Orzack et al (2015), ART included both IVF and ICSI, and the sex ratio was determined for the combined IVF-and ISCI-produced embryos. In most previous studies, the sex ratios of IVF-or ICSI-produced embryos/offspring were analyzed separately, and IVF was shown to result in a male-biased sex ratio (Avery et al 1991, Gutierrez-Adan et al 2001, Wrenzycki et al 2002, Dean et al 2010, Maalouf et al 2014, Torner et al 2014, while ICSI resulted in a female-biased sex ratio (Bu et al 2014, Maalouf et al 2014, Tarin et al 2014. Therefore, ICSI and IVF may affect sex ratios via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reporting long-term consequences of in vitro culture or other ART identified a sex bias in the frequency and nature of the long-term effect (FernandezGonzalez et al 2004, Sjoblom et al 2005, Feuer & Rinaudo 2012, Tarin et al 2014. These deleterious effects have pointed to epigenetic alterations produced by ARTs.…”
Section: Sex-specific Long-term Effects Mediated By Assisted Reproducmentioning
confidence: 99%